PKM Hukum Strategi Pencegahan Serta Membangun Kesadaran Publik Terhadap Bahaya Judi Online - juhandijuhandi; Farid Umam; Anggi Nopian; Aam Aditia; Siti Hajar (Nusantara Mengabdi Kepada Negeri, 2024)
As time goes by and changes in technology also change behavior in society. The impact of technology is not only positive but also negative, one of which is online gambling or slots which is currently popular in society, especially among teenagers. The aim of this PKM in the field of law is one of the KKM programs for students from group 42 of Bulakan Village, Bina Bangsa University as a form of awareness of online gambling which has a negative impact. The method for implementing PKM this time is holding a legal seminar on the dangers of online gambling specifically for teenagers as the target participants considering that there are many online gamblers among teenagers. The results of this PKM conclude that there is a negative impact on online gambling players and online gambling players can be caught in the Law on conventional gambling and the Information and Electronic Technology (ITE) Law.